Assessing canopy performance using carbonyl sulfide measurements. (17th April 2018) - Yang, Fulin; Qubaja, Rafat; Tatarinov, Fyodor; Rotenberg, Eyal; Yakir, Dan
Abstract: Carbonyl sulfide (COS) is a tracer of ecosystem photosynthesis that can advance carbon cycle research from leaf to global scales; however, a range of newly reported caveats related to sink/source strength of various ecosystem components hinder its application. Using comprehensive eddy‐covariance and chamber measurements, we systematically measure ecosystem contributions from leaf, stem, soil, and litter and were able to close the ecosystem COS budget. The relative contributions of nonphotosynthetic components to the overall canopy‐scale flux are relatively small (~4% during peak activity season) and can be independently estimated based on their responses to temperature and humidity. Converting COS to photosynthetic CO2 fluxes based on the leaf relative uptake of COS/CO2, faces challenges due to observed daily and seasonal changes. Yet, this ratio converges around a constant value (~1.6), and the variations, dominated by light intensity, were found unimportant on a flux‐weighted daily time‐scale, indicating a mean ratio of daytime gross‐to‐net primary productivity of ~2 in our ecosystem. The seasonal changes in the leaf relative uptake ratio may indicate a reduction in mesophyll conductance in winter, and COS‐derived canopy conductance permitted canopy temperature estimate consistent with radiative skin temperature. These results support the feasibility of using COS as a powerful and much‐needed means of assessing ecosystem function and its response to change. Abstract : Carbonyl sulfide (COS) is a potentially powerful tracer of photosynthesis and canopy conductance. We measured ecosystem contributions of COS from leaf, stem, soil and litter in a lemon orchard over the seasonal cycle, and were able to close the ecosystem COS budget, and show good agreement of COS derived GPP, canopy conductance, and canopy skin temperature with corresponding indirect estimates. Our results support the feasibility of the COS application to ecosystem process studies.